Important Medicinal Plants of Western Ghats: A Review - J. Malavika (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The Western Ghats, also known as the Sahyadrirange, is a mountain range that runs along the western coast of the Indian subcontinent. It stretches over a distance of about 1,600 kilometers (990 miles) from the southern part of India in Tamil Nadu to the state of Gujarat. The Western Ghats is considered as one of theworld’s major biodiversity hotspots. It is home to numerous endemicflora and fauna, including many rare and endangered species.